A preoperative prognostic model to predict surgical success in patients with perihilar cholangiocarcinoma. Issue 3 (21st August 2018) - Gaspersz, Marcia P.; Buettner, Stefan; Roos, Eva; van Vugt, Jeroen L.A.; Coelen, Robert J.S.; Vugts, Jaynee; Wiggers, Jimme K.; Allen, Peter J.; Besselink, Marc G.; Busch, Olivier R.C.; Belt, Eric J.; D'Angelica, Michael I.; et al.
Abstract : Background: Patients with resectable perihilar cholangiocarcinoma (PHC) on imaging have a substantial risk of metastatic or locally advanced disease, incomplete (R1) resection, and 90‐day mortality. Our aim was to develop a preoperative prognostic model to predict surgical success, defined as a complete (R0) resection without 90‐day mortality, in patients with resectable PHC on imaging. Study Design: Patients with PHC who underwent exploratory laparotomy in three tertiary referral centers were identified. Multivariable logistic regression was performed to identify preoperatively available prognostic factors. A prognostic model was developed using data from two European centers and validated in one American center. Results: In total, 671 patients with PHC underwent exploratory laparotomy. In the derivation cohort, surgical success was achieved in 102 of 331 patients (30.8%). No resection was performed in 176 patients (53.2%) because of metastatic or locally advanced disease. Of the 155 patients (46.8%) who underwent a resection, 38 (24.5%) had an R1‐resection. Of the remaining 117 (35.3%), 15 (12.8%) had 90‐day mortality. Independent poor prognostic factors for surgical success were identified, and a preoperative prognostic model was developed with a concordance index of 0.71. External validation showed good concordance (0.70). Conclusion: Surgical success was achieved in only 30% of patients with PHC undergoing exploratory laparotomy and could be predicted by age, cholangitis, hepatic artery involvement, lymph node metastases, and Blumgart stage.